Adoption of social networks as Web 2.0 citizen engagement tool in the local e-government context - Rexhepi, Artan; Filiposka, Sonja; Trajkovik, Vladimir (Inderscience Publishers, 2021)
Information and communication technology (ICT) in public administration is typically used for the purpose of e-government service implementation that provides strengthening of certain democratic functions. Recognising this, most of local government institutions (LGI) utilise ICT for services implementations and building relationship with stakeholders and citizens, allowing the adoption of Web 2.0 tools as platforms for promoting the public dialogue and participation in decision and policy making. This paper explores the e-participation implementation through usage of Web 2.0 tools in context of Kosovo LGIs from perspective of usage practices and potential relationships with citizen engagement. We have argued that the LGI online activity is an important factor influencing citizen engagement. Different set of metrics were examined to obtain relevant dimensions of citizens' reactivity and dialogue engagement. The analysis has not shown any significant correlation between the LGI activity and overall citizen engagement level. Implications and importance of those findings are discussed.
Keywords: e-participation adoption; e-governance; e-government; ICT tools; social media; social networks; Web 2.0; citizen engagement